Meganyctiphanes norvegica - Grams, Markus; Klinger, Michael; Richter, Stefan (Zenodo, 2023)
MEGANYCTIPHANES NORVEGICA The first pair of thoracopods (Fig. 7A) to Thp7 are all similar, whereas Thp8 is vestigial. The following descriptions are based on a detailed examination of the right Thp1 of three adult females of M. norƲegica . Cuticle and skeletal structures of thoracopods in M. norvegica The following description refers collectively to Thp1–7, if not specified otherwise. The ventral cuticle of the first thoracomere is coalesced with that of the cephalon. The density of the cuticle of this cephalothoracic sternum appears higher than in the posterior thoracomeres. Anteriorly, the thoracic cuticle articulates with the maxilla, which is tightly fitted against the anterior wall of the coxa and basis of Thp1. In all thoracomeres, the posterior thoracic cuticle is folded in an anterior direction, forming a broad roof-like apodeme (partly dashed curved arrow in Fig. 7B, C) of moderate density that hangs over the posterior half of the proximal foramen of the leg (i.e. of the coxa). Medially, the cuticle of the thorax forms a posterolaterally and dorsally directed finger-like extension (dashed black outline on Th in Fig. 7B). The protopod of M. norƲegica comprises a coxa (onethird) and a subdivided basis (two-thirds of the total length of the protopod). The coxa is predominantly made up of its more solid distal margin, which forms a half-ring reaching from posterior over medial to anterolateral (Co in Fig. 7D), where it connects to a plate of less dense cuticle. From the anterolateral corner of this plate, a solid cuticular beam reaches dorsad (Cb in Fig. 7C, D) and articulates with the thorax (*l in Fig. 7B–D). Posterolateral on the coxa, an epipod arises, which on Thp1 is plate-like (Ep in Fig. 7A, B), extending somewhat dorsad, but mostly ventrad (almost reaching the exopod). On the posterior thoracopods, the epipod splits into two coiled branches (one dorsal and one ventral) that ramify into several smaller filaments; on Thp6–8, the epipods show the highest complexity, with an additional ventral ...